Komunikasi Budaya Patriarki dalam Etnis Batak di Kota Medan: Studi Kasus Keluarga Bapak Sulaiman - Andini, Andini; Syahminan, Mhd (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Patriarchal culture glorifies masculinity and subordinates women, influencing their career choices and ambitions. Patriarchal culture oppresses women. Patriarchal society destroys and isolates women. Verbal and pictorial data are presented in this descriptive qualitative research. This research aims to analyze how patriarchal culture shackles and discriminates against women. Patriarchal society degrades women and inhibits their socialization. This descriptive qualitative research presents data verbally and graphically. In micro studies, social sciences and humanities apply qualitative research. The research was conducted at Jalan Tangguk Kec Medan Denai. The research started in early June and ended. Researchers obtained data through interviews, observations, and document studies. The results showed that Batak patriarchal culture empowers men at home and in society. Although Batak culture devalues women, they complement men. Batak families depend on men, while women clean the house. Batak people in Medan City can promote gender equality and progress through knowledge and action.